The interdependence of religion and the ruler And its political repercussions in Ancient Yemen - Abood Sammar, saad (Journal of College of Education, 2020)
In this study, we will highlight the dualism of the ruler and religion in ancient Yemen, and the manifestations of this dualism politically, and we will review the contribution of religion to the consolidation of the state in its three pillars (God, the ruler and the people). And the influence of religion on the formation of political unions, this study is also concerned with showing the role of the temple in strengthening the ruler’s authority, and how myths of religion portray that the ruling god protects cities and royal palaces.